累乗×等比型の数列の和を考えてみよう。
r は 1ではないとする。
\(\displaystyle{S_n=\sum_{k=1}^{n}k^2r^{k-1}}\),
\(\displaystyle{T_n=\sum_{k=1}^{n}kr^{k-1}}\),
\(\displaystyle{U_n=\sum_{k=1}^{n}r^{k-1}}\) とおく。
まず,数列{nrn-1} の和を再考してみる。
\(kr^k-(k-1)r^{k-1}=(r-1)kr^{k-1}+r^{k-1}\) … ①
に注目する。
① より
\(\displaystyle{\sum_{k=1}^n\left(kr^k-(k-1)r^{k-1}\right)
=\sum_{k=1}^n\left((r-1)kr^{k-1}+r^{k-1}\right)}\)
ここで,
\(\displaystyle{\sum_{k=1}^n\left(kr^k-(k-1)r^{k-1}\right)
=nr^n}\)
\(\displaystyle{
\sum_{k=1}^n\left((r-1)kr^{k-1}+r^{k-1}\right)
=(r-1)T_n+U_n}\)
ゆえに
\((r-1)T_n=nr^n-U_n\)
数列{n2rn-1} の和は同様に
\(k^2r^k-(k-1)^2r^{k-1}=(r-1)k^2r^{k-1}+2kr^{k-1}-r^{k-1}\) … ②
に注目すると,
\((r-1)S_n=n^2r^n-2T_n+U_n\)
例えば,
\(\displaystyle{S_n=\sum_{k=1}^{n}k^2\cdot 2^{k-1}}\),
\(\displaystyle{T_n=\sum_{k=1}^{n}k\cdot 2^{k-1}}\),
\(\displaystyle{U_n=\sum_{k=1}^{n}2^{k-1}}\) とおく。
\(S=n^2\cdot 2^n-2T_n+U_n\)
\(=n^2\cdot 2^n - 2(n\cdot 2^n-U_n)+U_n\)
\(=n^2\cdot 2^n - 2n\cdot 2^n+3U_n\)
\(=n^2\cdot 2^n - 2n\cdot 2^n+3(2^n-1)\)
\(=(n^2-2n+3)\cdot 2^n - 3\)
まとめると,
\(\displaystyle{S_n=\sum_{k=1}^{n}k^2r^{k-1}}\),
\(\displaystyle{T_n=\sum_{k=1}^{n}kr^{k-1}}\),
\(\displaystyle{U_n=\sum_{k=1}^{n}r^{k-1}}\) とおく。
\((r-1)U_n=r^n-1\)
\((r-1)T_n=nr^n-U_n\)
\((r-1)S_n=n^2r^n-2T_n+U_n\)